Identifikasi Konsep Arsitektur Hijau di Permukiman DAS Brantas Kelurahan Penanggungan Malang - Asikin, Damayanti; Handajani, Rinawati P.; Pamungkas, Sigmawan Tri; Razziati, Haru A. (Jurnal Ruas, 2013)
The review was conducted to identify the concept of green architecture in the area of settlement on Watershed (DAS) Brantas Malang as informal settlements. Using the Theory of Ekistics - Doxiadis, acquisition search results of initial study settlements forming elements such as: a) Nature: rivers, topography, green open space, building orientation, and building density; b) Shells: housing / residential and public facilities; and c) Networks: drainage system, toilets, utility networks. Parameters used green architecture concept based on the concept of green architecture for residential and Greenship Rating Tools For Building Built Version 1.0.O. The natural environment have 2 parameters with a maximum value of 4; the protection element have 2 parameters with a maximum value of 2, and the network element have 4 parameters with a maximum value of 10. Assessment parameters on the protection element reaches a maximum value of 1.5 from 2 or 75% due to the utilization of the potential of the river as a public facility - Recreational fishing is also using the building with natural materials and shaped shelter is open. While actual network elements is the dominant element in this region does not reach the maximum value has not been used optimally due to the natural potential, especially rivers, to improve environmental quality. While elements of the natural environment to obtain the smallest value due to the relatively high density of buildings and the neighborhood was developed without planning.Keywords: concept of green architecture, Brantas Watershed Settlement, Malang